IMPLEMENTATION OF COMMUNITY NURSE CARE BEHAVIOR TOWARDS COVID-19 REACTIVE SELF-Isolation PATIENTS AT LAWIR PUSKESMAS IN 2021 - Handi, Heribertus; Henny Mariati, Lusia; Dewiyanti Wea, Lidwina; Romana Iwa, Kornelia; Fariday Dewi, Claudia; Y. Demang, Fransiska; Masri Rada, Egis; Roida Eka, Angelina (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2022)
Community service program for nursing study program lecturers with the theme "Implementation of caring behavior for community nurses for COVID-19 reactive self-isolation patients at Lawir Health Center in 2021" Caring behavior is an attitude, caring, respect, and respect for others, which means giving more attention to someone and how that person acts. Nurses need to carry out caring behavior for COVID-19 reactive self-isolation patients. Nurses understand the needs and problems of COVID-19 isolation patients through good and correct therapeutic communication so that the impact of caring for patients will get the satisfaction that their health needs are met. The purpose of this community service is to train nurses at the Lawir Public Health Center on how to care for community nurses towards COVID-19 self-isolation patients so that isolation patients' satisfaction with nursing care services is fulfilled. This caring behavior implementation training activity was attended by all nurses on duty at the Lawir Health Center so that the quality of nursing care services was at the forefront in health services for the recovery of COVID-19 reactive patients in the region. This community service activity will be carried out from October to January with simulation and demonstration methods. It is hoped that all nurses should improve their caring behavior towards COVID-19 patients so that the impact of satisfaction with nursing services on COVID-19 patients at the Lawir Health Center will be seen.